Correlation analysis of relative chlorophyll content and yield of maize hybrids of different genotypes - Zagyi, Péter; Tamás, András; Rácz, Dalma; Fejér, Péter; Radócz, László; Horváth, Éva (Acta Agraria Debreceniensis, 2022)
In 2021, correlation between relative chlorophyll content and yield in three maize hybrids of different genotypes was examined. The data were collected at the Látókép Experimental Station of the University of Debrecen located on the Hajdúság loess ridge in Hungary. The soil of the small plot field strip plot trial, which was set up in 2011, was calcareous chernozem. Apart from the control treatment (without fertilisation), N fertiliser is applied in the form of base and top dressing. The base fertiliser containing 60 and 120 kg ha-1 N of nutrient applied in spring was followed by top dressing containing +30–30 kg ha-1 N in V6 and V12 phenophases. SPAD values measured at different phenological stages of the growing season increased by an average of about 28% up to 10 leaf stage for all three hybrids. In the pre-silking period (Vn), the relative chlorophyll content decreased by 8% on average. After an average increase of 14% in the tasselling and silking period, SPAD decreased by an average of about 29% at full maturity (R6).For the different fertiliser treatments, higher N doses resulted in higher yields. In the basal fertiliser treatment, the A 60 N dose resulted in an average 34% increase in yield, and the A 120 N dose resulted in an average 94% increase in yield compared to the control. The 60 kg ha-1 N basal fertiliser (A60) increased in the V6 phenophase with an additional 30 kg ha-1 N resulted in an average yield increase of 26%. When 120 kg ha-1 N of basal fertiliser (A120) was increased by an additional 30 kg ha-1 N in the V6 phenophase, only the Merida hybrid showed a significant yield increase (7%). No further yield increase was observed when V690 and V6150 treatments were increased by an additional 30 kg ha-1 N in the V12 phenophase. The yield of the Armagnac hybrid decreased by almost 20%, the yield of Fornad by 3% and the yield of Merida by 1%.